Fabrication of cellulose/graphene paper as a stable-cycling anode materials without collector. (15th March 2018) - Zhang, Chunliang; Cha, Ruitao; Yang, Luming; Mou, Kaiwen; Jiang, Xingyu
Highlights: Cellulose/graphene paper is fabricated by wet end formation. Cellulose/graphene paper have excellent charge-discharge stability. Cellulose/graphene papers has good mechanical properties and thermal stability. Cellulose/graphene papers can be directly employed as anode. Abstract: Flexible and foldable devices attract substantial attention in low-cost electronics. Among the flexible substrate materials, paper has several attractive advantages. In our study, we fabricate cellulose/graphene paper by wet end formation (papermaking). The cationic polyacrylamide remarkably improve the retention ratio of graphene of cellulose/graphene slurry. Besides, cellulose/graphene paper exhibits well mechanical properties such as its flexibility and folding endurance. And we replace copper foil collector with cellulose/graphene paper in lithium-ion batteries without collector, and investigate its electrochemical properties. The obtained results show that cellulose/graphene paper presents excellent charge-discharge stability after 1600th cycles as the anode of lithium-ion batteries. These advantages highlight the potential applications of cellulose/graphene paper as anode materials for lithium-ion batteries.